2007
DOI: 10.1118/1.2761342
|View full text |Cite
|
Sign up to set email alerts
|

TU‐C‐M100F‐01: Development of a Linac‐MRI System for Real‐Time ART

Abstract: Purpose: To describe the novel design of the coupling an of MRI to a medical linac to provide real‐time tracking of the tumor and healthy tissues during irradiation by the treatment beam Method and Materials: Various embodiments are defined in our patents (Fallone, Carlone, Murray) to avoid mutual interference between the MR and the linac. Our method allows rotation of a linac with respect to the subject to allow irradiation of the subject from any angle without disturbing the magnet homogeneity. Magnetic shie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 0 publications
0
54
0
Order By: Relevance
“…This is of particular importance not only for treatment systems with longer system latencies but also with the realization of more complex image-guided radiotherapy systems under development that are subject to larger system latencies. [26][27][28][29] RMSE for diaphragm respiratory prediction was higher than abdominal wall respiratory prediction RMSE. This is potentially due to the lower sampling rate of diaphragm respiratory data (5 Hz) compared to abdominal wall respiratory data (30 Hz); a previous study by Ren et al found that a lower sampling rate resulted in a reduction in prediction accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…This is of particular importance not only for treatment systems with longer system latencies but also with the realization of more complex image-guided radiotherapy systems under development that are subject to larger system latencies. [26][27][28][29] RMSE for diaphragm respiratory prediction was higher than abdominal wall respiratory prediction RMSE. This is potentially due to the lower sampling rate of diaphragm respiratory data (5 Hz) compared to abdominal wall respiratory data (30 Hz); a previous study by Ren et al found that a lower sampling rate resulted in a reduction in prediction accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…The method described in this paper has been applied to the optimal design of an open compact 0.5 T biplanar superconducting magnet assembly for potential use in the linac-MRI system currently pursued by our group [38]- [40]. The geometry of the magnet assembly and linac arrangement is illustrated in Fig.…”
Section: Optimization Examplementioning
confidence: 99%
“…Advances in radiation-therapy rely on the improvements in the supporting technology: medical accelerators, robotic systems, various imaging and monitoring systems, as well as radiation-therapy planning and delivery software. Recent technological advancements in radiation oncology are directed towards several overlapping goals [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]: (i) integrating of these multiple-modality systems, (ii) increasing the overall spatial and dosimetric accuracy of the treatment and decreasing treatment time, (iii) miniaturizing and decreasing the cost of the hardware, and (iv) developing new treatment machines for more specific tumor sites and/or applications. Future compact-design and low-cost linacs fall directly under the last three categories.…”
Section: Implication On Medical Acceleratorsmentioning
confidence: 99%